Fashion Design Center Di Pekanbaru Dengan Pendekatan Arsitektur Kontemporer - Iin Fitri Febriani; Wahyu Hidayat; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Fashion is a lifestyle that is in high demand by today's society. The development of fashion becomes important in various circles both young and old. The development of the world of fashion must be supported by quality human resources in the field of fashion. The designers have a problem in terms of introducing their designs to the public because of the lack of facilities and the provision of space or containers for fashion design enthusiasts in Pekanbaru, it will be designed a forum for fashion design enthusiasts to learn and promote the design results to the public. This building was designed using contemporary architectural themes that are applied into buildings. The explanation of contemporary architectural themes is to use contemporary principles.Keywords : Fashion, Design, Contemporary